Banks, markets, and efficiency - Falko Fecht; Antoine Martin (Federal Reserve Bank of New York, 2005)
In this paper, we address the question whether increasing households' financial market access improves welfare in a financial system in which there is intense competition among banks for private households' funds. Following earlier work by Diamond and by Fecht, we use a model in which the degree of liquidity insurance offered to households through banks' deposit contracts is restrained by households' financial market access. However, we also assume spatial monopolistic competition among banks. Because monopoly rents are assumed to bring about inefficiencies, improved financial market access that limits monopoly rents also entails a positive effect; however, this beneficial effect is only relevant if competition among banks does not sufficiently restrain monopoly rents already. Thus, our results suggest that in Germany's bank-dominated financial system, which is characterized by intense competition for households' deposits, improved financial market access might reduce welfare because it only reduces risk sharing. In contrast, in the U.S. banking system, where there is less competition for households' deposits, a high level of household financial market participation might be beneficial.
Keywords: E44; G10; G21; 330; financial intermediaries; risk sharing; banking competition; comparing financial systems; Finanzmarkt; Privater Haushalt; Bank; Wettbewerb; Monopolistischer Wettbewerb; Wohlfahrtsanalyse; Deutschland